2022
DOI: 10.1007/s11301-021-00253-6
|View full text |Cite
|
Sign up to set email alerts
|

Hidden champions: a review of the literature & future research avenues

Abstract: Substantial efforts have contributed to overcome the scarcity of research on hidden champions. Nevertheless, literature has yet missed to compile a comprehensive review. Drawing on the insights of 112 publications, four strands of literature could be distinguished to unravel the essence of hidden champions. Research on hidden champions studies their (1) internationalization strategies, (2) R&D and innovation strategies, the (3) worldwide and regional geographic distribution of hidden champions and finally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 174 publications
1
13
0
Order By: Relevance
“…Concerning our theoretical contribution, we add to the small and emerging stream of HC literature, as we examine the HC phenomenon on a regional level. Previous research on HCs has mainly focused on the internationalization (e. g. Audretsch et al 2018), R&D, and innovation (e. g. Rammer/Spielkamp 2015, 2019) strategies of HCs, as identified by Schenkenhofer (2020). A rather small strand of the literature analyzes HCs in a geographic context, examining, for instance, the worldwide distribution of HCs (e. g. Audretsch et al 2020;Lehmann et al 2019) or the role of HCs in small towns and peripheral regions (e. g. Lang et al 2019;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning our theoretical contribution, we add to the small and emerging stream of HC literature, as we examine the HC phenomenon on a regional level. Previous research on HCs has mainly focused on the internationalization (e. g. Audretsch et al 2018), R&D, and innovation (e. g. Rammer/Spielkamp 2015, 2019) strategies of HCs, as identified by Schenkenhofer (2020). A rather small strand of the literature analyzes HCs in a geographic context, examining, for instance, the worldwide distribution of HCs (e. g. Audretsch et al 2020;Lehmann et al 2019) or the role of HCs in small towns and peripheral regions (e. g. Lang et al 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain a market-leading position, they manufacture technologically advanced products and position themselves as quality leaders. Consequently, HCs require profound expertise, which they have acquired mainly due to their qualified workforce and extensive innovation activities (e. g. Lehmann et al 2019;Rammer/Spielkamp 2015Schenkenhofer 2020). Third, niche firms stand out by applying specialization and differentiation, typically with reference to products and customers (e. g. Audretsch et al 2018Audretsch et al , 2020Dalgic/ Leeuw 1994;Kotler 1997).…”
Section: The Hidden Champions Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a comprehensive review of the increasing Hidden Champions literature is missing. Schenkenhofer’s ( 2022 ) study “Hidden Champions: a review of the literature & future research avenues” closes this research gap by investigating 112 publications on Hidden Champions. Using a conceptual and theory-based review, the author derives the factors that explain the characteristics and behavior of Hidden Champions and identifies the main research streams.…”
Section: The Articles In the Special Issuementioning
confidence: 99%
“…However, it would be interesting to dive into some of the underlying factors that contribute to the explanation of their success. A recent review identified the quality of human capital (particularly at the managerial level), innovation in form of patented proprietary technologies, and nimbleness (a combination of flat organization structure with relatively small size) as the most distinct resources controlled by hidden champions (Schenkenhofer, 2022). Technological developments also play a role; recent experimental research has shown additive manufacturing techniques, such as 3D printing, to significantly reduce the levels of output required to access the full extent of economies of scale (Baumers & Holweg, 2019).…”
Section: But Do We Need Champions?mentioning
confidence: 99%